2006
DOI: 10.1038/nphys458
|View full text |Cite
|
Sign up to set email alerts
|

Initialization and read-out of spins in coupled core–shell quantum dots

Abstract: I n the field of quantum information science, semiconductor quantum dots (QDs) are of particular interest for their ability to confine a single electron for use as a qubit 1,2. However, to realize the potential offered by quantum information processing, it is necessary to couple two or more qubits. In contrast to coupling individual QDs, we demonstrate the integration of two coupled electronic states within a single QD heterostructure. These chemically synthesized nanocrystals, known as quantumdot quantum well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Its optical initialization, readout, and manipulation have been the center of important investigations. [1][2][3][4][5][6][7][8] At the same time, theoretical and experimental studies have shown that the hyperfine coupling with the lattice nuclei spins is the ultimate limit, at low temperature, to the electron-spin relaxation or decoherence in QDs, leading to typical ensemble dephasing times of the order of 1 ns in III-V QDs. [9][10][11][12] Up to now, the studies have been centered on the spin of a conduction electron and only recently several experiments have evidenced the initialization and the readout of hole spins confined in QD nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Its optical initialization, readout, and manipulation have been the center of important investigations. [1][2][3][4][5][6][7][8] At the same time, theoretical and experimental studies have shown that the hyperfine coupling with the lattice nuclei spins is the ultimate limit, at low temperature, to the electron-spin relaxation or decoherence in QDs, leading to typical ensemble dephasing times of the order of 1 ns in III-V QDs. [9][10][11][12] Up to now, the studies have been centered on the spin of a conduction electron and only recently several experiments have evidenced the initialization and the readout of hole spins confined in QD nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…They mainly consisted of II-VI, IV-VI, and III-V compounds and can be presented, such as CdS/HgS/CdS, ZnS/CdS/ZnS, CdSe/HgSe/CdSe, CdTe/ HgTe/CdTe, CdS/PbS/CdS, PbSe/CdS/PbSe, PbSe/CdSe/ PbSe, AlAs/GaAs/AlAs/, InP/InAs/InP, etc. heterostructures (see for e.g., (Balandin and Wang 2006;Schmid 2010;Rogach 2008;Hofman 2009;Eychmuller et al 1993;Schooss et al 1994;Mews et al 1996;Hause et al 1993;Bryant 1995;Little et al 1998;Braun et al 2001;Bryant and Jaskolski 2003;Perez-Conde and Bhattacharjee 2006;Berezowsky et al 2006;Weng et al 2009;Guo-Yi 2004;Royo et al 2007;Brovelli et al 2011;Jia 2011;SalmanOgli and Roatami 2011) and references therein).The QDQW structure involves an onion-like nanosystem composed of a quantum dot core surrounded by two or more shells of alternating narrower and wider band gap materials. The original feature of QDQW is that their physical properties can be controlled and can be tuned by changing the core radius, the thickness of the quantized layer and the size of the outermost shell.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is clear that the study of states of charge carriers in the internal QW of such barrier/well/barrier structures under the different physical conditions is of a separate interest. From this point of view in several papers in the frameworks of various approximations are being discussed the electronic, hole (Eychmuller et al 1993;Schooss et al 1994;Mews et al 1996;Hause et al 1993;Bryant 1995;Little et al 1998;Braun et al 2001;Bryant and Jaskolski 2003;Perez-Conde and Bhattacharjee 2006), excitonic (Kim et al 2006;Cat et al 2009;Prasad 2004;Heng and Jun-Jie 2004;Kai and Xia (1998); Jun-Jie (2002)) and phonon (Berezowsky et al 2006;Weng et al 2009;Guo-Yi 2004;Royo et al 2007) states, as well as the optical absorption and luminescence spectra (Eychmuller et al 1993;Schooss et al 1994;Mews et al 1996;Hause et al 1993;Bryant 1995;Little et al 1998;Braun et al 2001;Kim et al 2006;Cat et al 2009;Prasad 2004;Porteanu et al 2001;Fang et al 2010) of QDQW structures.…”
Section: Introductionmentioning
confidence: 99%
“…The strong size-dependent electronic properties in QDs are compatible with modern optoelectronics. 1,2 Electron spins manipulation and coherent control in semiconductor QDs has been received increasing attention during the past decades due to both the fascinating physics [3][4][5][6][7] and the potential applications in spin-based nano-to micro-scale devices for spintronics and quantum computation. 8,9 The all-optical time-resolved magneto-optical (MO) Faraday effect (transmission geometry) and the time-resolved MO Kerr effect (reflection geometry) are well suited to investigate the spin dynamics in a broad spectrum, regardless of the photoluminescence efficiency.…”
Section: Introductionmentioning
confidence: 99%